Analysis of Product Differentiation, Brand Image, and Consumer Perceptions of Purchasing Decisions in E-Commerce - Farid Hilmi Najim, M.; Adji Kusuma, Kumara; Komala Sari, Dewi (Journal Research of Social Science, Economics, and Management, 2026)
The fast growth of online shopping has altered the ways in which consumers typically make purchases. The main objective of this study is to examine how product uniqueness, brand image, and customer feelings influence online shopping behavior. One hundred participants from the Management Study Program at Muhammadiyah University of Sidoarjo were interviewed using a purposive sampling method in this quantitative study. Multiple linear regression in SPSS was used to analyze the data. The study showed that the three factors have a positive and significant effect on purchasing decisions, with their respective levels of significance: product differentiation (t = 2.603; p = 0.011), brand image (t = 9.038; p = 0.000), and consumer perception (t = 9.534; p = 0.000). Consumer perception is the most dominant variable. The conclusion of this study emphasizes the importance of differentiation strategies, strengthening brand image, and understanding consumer perception. The implication is that e-commerce players need to focus on product value and customer experience to increase loyalty and sales.